2018
DOI: 10.18632/oncotarget.25694
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death: the battlefield between the host and alpha-herpesviruses and a potential avenue for cancer treatment

Abstract: Programed cell death is an antiviral mechanism by which the host limits viral replication and protects uninfected cells. Many viruses encode proteins resistant to programed cell death to escape the host immune defenses, which indicates that programed cell death is more favorable for the host immune defense. Alpha-herpesviruses are pathogens that widely affect the health of humans and animals in different communities worldwide. Alpha-herpesviruses can induce apoptosis, autophagy and necroptosis through differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 155 publications
0
10
0
Order By: Relevance
“…Apoptosis regulates embryonic development, cell turnover, and the immune response against tumor or virus-infected cells [48, 49]. Virus-induced cell apoptosis is involved in the pathogenesis of many viral infections [50, 51]. Our laboratory has discovered that DEV can induce apoptosis in the thymus, spleen and pancreatic lymphocytes of adult ducks and can cause apoptosis in DEFs in vitro [52, 53], and further confirmed that the mRNA levels and enzymatic activities of caspase-3, caspase-7 and caspase-9 were significantly increased during DEV-induced cell apoptosis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis regulates embryonic development, cell turnover, and the immune response against tumor or virus-infected cells [48, 49]. Virus-induced cell apoptosis is involved in the pathogenesis of many viral infections [50, 51]. Our laboratory has discovered that DEV can induce apoptosis in the thymus, spleen and pancreatic lymphocytes of adult ducks and can cause apoptosis in DEFs in vitro [52, 53], and further confirmed that the mRNA levels and enzymatic activities of caspase-3, caspase-7 and caspase-9 were significantly increased during DEV-induced cell apoptosis [53].…”
Section: Discussionmentioning
confidence: 99%
“…Among these mechanisms, apoptosis is commonly used by diverse infectious agents to negatively control immune responses by inducing cell death in inflammatory cells (280)(281)(282)(283)(284)(285)(286)(287). The high-affinity recognition of autoantigens by T lymphocytes (when these are constantly stimulated by antigens) can lead to apoptosis (280,(288)(289)(290)(291)(292)(293)(294)(295)(296)(297). There are two major apoptotic pathways, and both involve the deletion of peripheral and mature immune cells.…”
Section: The Role Of Cell Death In Homeostasis and The Control Of Thementioning
confidence: 99%
“…Alpha-herpes viruses can induce apoptosis, autophagy and necrosis through different molecular mechanisms. These pathways in luence infection and replication of alpha-herpes viruses and therefore they may become additional candidates for cancer therapy [37]. As an ef icient oncolytic virus, herpes simplex virus (HSV) has the following advantages: (1) quick replication in cells and infection of multiple types of cancer cells, (2) easy modi ication and insertion of its large genome, (3) prevention by antiviral agents, (4) modi ication of its glycoprotein can improve targeting of tumor cells, and (5) ability to escape the immune response of the host in order to: (a) complement and incapacitate immune globulins via viral glycoproteins, (b) block maturation of antigen presenting cells, (c) inhibit production of cytokines and chemokines from infected cells, (d) evade the host immunological surveillance, and (e) inhibit cell death and apoptosis induced by cytotoxic T-lymphocytes [35].…”
Section: Oncolytic Viruses and The Rising Role Of Vzvmentioning
confidence: 99%